PENINGKATAN KINERJA GURU SEKOLAH DASAR MELALUI SUPERVISI AKADEMIK - Muryanti Muryanti (Universitas Ngudi Waluyo, 2021)
The purpose of this study was to improve teacher performance through academic supervision at SD Negeri 3 Kesambi, Mejobo District, Kudus Regency in the 2019/2020 school year. The school action research was carried out in 2 cycles, each cycle of four stages, namely planning, implementing, observing and reflecting. There was an increase in teacher performance at SDN 3 Kesambi. Before being given the action, the percentage of the professional competence of the teacher only reached a percentage of 50% with poor criteria. In the first cycle it increased to 67% with good enough criteria. In the second cycle it has increased to 80.19% with very good criteria. So it can be concluded that academic supervision improves the performance of SDN 3 Kesambi teachers.